Sarong MSMEs in push local economic growth in Gresik City - Muhammad Afifi Rahman (Privietlab, 2026)
This study examines the strategic role of sarong Micro, Small, and Medium Enterprises (MSMEs) in promoting local economic growth in Gresik City, East Java. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving MSME owners, workers, and local consumers. The findings reveal that most sarong MSMEs are family-based businesses that create significant local employment and income opportunities. Through innovation and digital marketing especially via social media platforms these enterprises expand their market reach while preserving traditional weaving motifs unique to Gresik’s cultural identity. Sarong MSMEs not only strengthen the local economy by utilizing local raw materials and labor but also empower women and sustain cultural heritage. However, key challenges persist, including limited access to capital, inadequate managerial and digital skills, and competition from industrial and imported products. Strengthening government support, enhancing digital literacy, and expanding financing access are essential for ensuring their sustainable growth. Overall, sarong MSMEs serve as both economic and socio-cultural agents that significantly contribute to inclusive local development in Gresik City.